Testing the Effectiveness of Ethanol Extract of Horse Whip Leaves (Stachytarpheta Jamaicensis L.) towards Wounds in Mice (Mus musculus) - Wulan Ratia Ratulangi; Zohroyani; En Purmafitriah; Baiq Ayu Aprilia Mustariani (Politeknik Medica Farma Husada Mataram, 2023)
The horse whip leaves plant (Stachytarpheta jamaincensis) is an annual herbaceous shrub. Cuts are wounds that occur due to cuts by instruments or sharps objects. This study aims to determine the effectiveness of the ethanol extract of horse whip leaves on the healing of cuts in mice (Mus musculus) and the most effective concentration for healing cuts in mice. Design This study uses laboratory experimental methods. The sample used for each experimental group was 5 mice with a total of 5 groups, so this study used 25 mice with 3 treatments, namely the treatment (positive control (+), negative control (-), 25%, 50%, 75%). All data is tabulated and statistically analyzed with ANOVA. The conclusion shows that the concentration of horsetail leaf extract at a concentration of 75% is the most effective in healing cuts in mice when compared to horsetail leaf extract at concentrations of 50% and 25% in terms of the average percentage of healing from day 1 to day 7.